Monoclonal Antibodies: from Development to Clinical Application - YuI Budchanov (Клиническая онкогематология)
The development of monoclonal antibodies (MABs) resulted in revolutionary achievements in diagnosing and treating of oncohematological disorders. The review dwells on the history of the development and improved technologies for production of monoclonal antibodies illustrated by anti-CD20-MABs which recognize different epitopes of the CD20 antigens and have a higher antitumor activity. Engineering techniques can contribute to understanding the effector mechanisms of the application of the novel anti-CD20-MABs and are intended for further improvement of the treatment results.